ANALISIS MISKONSEPSI SISWA PADA PEMBELAJARAN TOPIK PERUBAHAN WUJUD BENDA DI SDS PELANGI MEDAN - Enjelika Sihotang; Nurhairani; Fahrur Rozi; Edizal Hatmi; , Apiek Gandamana (STKIP Subang, 2026)
An Analysis of Students’ Misconceptions in Learning the Topic of Changes in States of Matter at SDS Pelangi Medan. Undergraduate Thesis. Primary School Teacher Education Study Program, Faculty of Education, Universitas Negeri Medan, 2026. This study aimed to describe the misconceptions of fifth-grade students at SDS Pelangi Medan regarding the concept of changes in states of matter, identify the factors contributing to these misconceptions, and describe the teacher’s efforts to overcome them. This study employed a qualitative approach with a case study design. The research subjects consisted of 15 fifth-grade students and one fifth-grade teacher at SDS Pelangi Medan. Data were collected through a diagnostic test based on the Certainty of Response Index (CRI), semi-structured interviews, and documentation. Data were analyzed using the Miles and Huberman model, which includes data reduction, data display, and conclusion drawing. The validity of the data was ensured through source triangulation and technique triangulation. The findings revealed that most students experienced misconceptions regarding the concepts of changes in states of matter. Out of 15 students, 12 were identified as having misconceptions, while 3 demonstrated an appropriate understanding of the scientific concepts. Misconceptions were found in the concepts of melting, freezing, evaporation, condensation, sublimation, and deposition. The identified misconceptions included the belief that evaporated water disappears completely, that water droplets on the outside of a cold glass come from water leaking through the glass, and that changes in states of matter produce new substances. Factors contributing to these misconceptions included students’ prior incorrect understanding, everyday experiences that conflicted with scientific explanations, limited use of concrete learning media, and a lack of experimental activities during instruction. The teacher’s efforts to address these misconceptions included re-explaining the material, providing concrete examples, conducting simple demonstrations, facilitating discussions, and engaging students in question-and-answer activities. The study concludes that misconceptions regarding changes in states of matter are still prevalent among fifth-grade students at SDS Pelangi Medan. Therefore, learning activities should emphasize direct experiences, the use of concrete learning media, and experimental activities to help students develop a more accurate conceptual understanding.